Sustainable Social Forestry in Bali (A Case Study at Hutan Desa Wanagiri) - Laksemi, Ni Putu Sekar Trisnaning; Sulistyawati, Endah; Mulyaningrum, Mulyaningrum (Department of Forestry, Faculty of Agriculture, University of Lampung, 2019)
The limited access to land, particularly for the community around the forest contributed to deforestation in Indonesia. This problem drives the emergence of social forestry. In fact, the implementation of social forestry in some cases could not be done sustainably. The research was conducted to identify the determinants of sustainable social forestry and analyze the implementation of sustainable social forestry in Hutan Desa Wanagiri, Bali. The analysis is carried out using Analysis Hierarchy Process (AHP) method. The study was conducted from December 2017 - May 2018. Based on the results of the study, three main principles were used to evaluate the management of Hutan Desa Wanagiri, namely the principle of sustainable environment (environmental aspects), improvement of community welfare (socio-economic aspects), and improvement of forest governance (institutional aspects). Based on the AHP results regarding the three principles, the level of sustainability of Hutan Desa Wanagiri for the environmental aspects is 49,9%, and then 62,7% for socio-economic aspect and 51% for institutional aspects. Overall, the level of sustainability of Hutan Desa Wanagiri is equal to 54,4% and classified as 'moderate sustainable'. Keywords: environment, Hutan Desa, institutional, socio-economic, sustainability